Marker Based Pose Estimation and Distance Measurement in Autonomous Vehicle - Meera Giridhar, Dr. S Gayathri (International Journal of Advanced Science and Technology, 2020)
Pose estimation is of great importance in robot navigation. This process is based on finding correspondences between points in the real environmentandtheirprojection.Fiducialmarkersare used for this purpose to make it easier. The distance thus measured based on pose estimation and marker identification can be used to locate different points or junctions in the map and helps in localizing a self- driving car. This project usesROS as a tool which provides a simulation and visualization tool to visualize the movement of the robot which can be correlated to the real- time scenario. The testing environments for the vehicle and performance evaluation are simulated using ROS which supports Gazebo simulator and other visualization tools.